INDIAN WRITERS IN ENGLISH IN PORTRAYAL OF POVERTY IN THE WORKS (International Journal of Food and Nutritional Sciences, 2023)
Poverty has been a major challenge that has remained in India. The impacts are broad with impact on the social and economic structure of the country. It leaves the individuals with a feeling of being grouped in two groups, the rich and the poor. Owing to their low-income, uneducated and limited resources, the poor are bound to work beneath the rich. When a man is not rich, he becomes emotionally, physically and psychologically ill. The Indian world-famous authors such as Bhabani Bhattacharya, Kamala Markandaya, Arundhati Roy, and Aravind Adiga reveal the poverty-stricken conditions in the contemporary Indian nation. The general aim of the paper is to explain how the callousness and the inability to empathize with the poor that characterizes the wealthy lead to violence, and their brutality, which makes the poor feel hopeless and out of context with the rest of the society. It also demonstrates the inability of the class differences to create conformity in the society.